2013
DOI: 10.1371/journal.pone.0054876
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency Response of the Vibrissae of Harp Seal, Pagophilus Groenlandicus, to Sound in Air and Water

Abstract: The motion of isolated seal vibrissae due to low frequency sound in air has been measured using a microscope with a video camera and modeled using an FEM method with good agreement between the measurements and the model; the model has also been used to predict the motion of seal vibrissae in water. The shape of the seal vibrissae is that of a tapered right rectangular prism, unlike that of the previously studied rat vibrissae which are conical in shape. Moreover, unlike rat vibrissae which oscillate in the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 14 publications
1
27
1
Order By: Relevance
“…Our values of Young’s modulus reported in this study were comparable to those of rat vibrissae, which ranged from 3–7.36 GPa [ 51 , 52 ]. Young’s modulus of harp seal vibrissae was previously measured at 1.8–3.3 GPa [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our values of Young’s modulus reported in this study were comparable to those of rat vibrissae, which ranged from 3–7.36 GPa [ 51 , 52 ]. Young’s modulus of harp seal vibrissae was previously measured at 1.8–3.3 GPa [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in air also found that seal vibrissae vibrated in response to stimulation from low frequency sounds [20]. When modeled with the appropriate drag coefficient for water, the vibrissae were predicted to be tuned to frequencies of 20 to 200 Hz.…”
Section: Introductionmentioning
confidence: 92%
“…The natural frequencies of whiskers shed by fur and harbor seals were measured [121,59]. They show a first mode of vibration at around 40-60Hz.…”
Section: Under the Skin: Nerve Responsementioning
confidence: 99%